The Everything Store: Jeff Bezos and the Age of Amazon - Brad Stone (New York Back Bay Books, 2014)
Amazon.com's visionary founder, Jeff Bezos, wasn't content with being a bookseller. He wanted Amazon to become the everything store, offering limitless selection and seductive convenience at disruptively low prices. To do so, he developed a corporate culture of relentless ambition and secrecy that's never been cracked. Until now. Brad Stone enjoyed unprecedented access to current and former Amazon employees and Bezos family members, and his book is the first in-depth, fly-on-the-wall account of life at Amazon. The Everything Store is the book that the business world can't stop talking about, the revealing, definitive biography of the company that placed one of the first and largest bets on the Internet and forever changed the way we shop and read.
Keywords: Business; Biography; Nonfiction; Technology